The study of troglitazone liver toxicity via in vitro and in silico approaches - Nuamah, M.F (2022)
Background: Drug-induced liver injury (DILI) is rare but potentially lethal, and it can cause liver disease attributable to all types of drugs. The adverse impact of most of the DILI incidents is mild, and it recovers after the removal of drugs. The harmful agents should be identified and removed as early as possible to avoid the development of chronic liver damage. Troglitazone (TGZ) was a derivative of a thiazolidinedione drug produced for the treatment of type 2 diabetes, in the late 1990s. However, it was withdrawn from the market due to reported cases of liver toxicities. Several molecular mechanisms have been proposed to underlie TGZ-induced liver toxicity. Understanding the interactions between these mechanisms could aid drug developers in predicting DILI more vigorously.